Elevating Teachers’ Competence through the Development of Instructional Media Oriented to Problem-solving Skills with the Aid of Articulate Storyline - Megahnia Prihandini, Rafiantika; Setiawani, Susi; Feri Widyawati, Yuli (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
With rapid technological advancement, integrating technology into education becomes increasingly important. It is thus imperative for teachers to master satisfactory competence in improving students' problem-solving skills. Fundamentally a community service, this study aims to increase teacher competence in developing instructional media oriented to problem-solving skills assisted by Articulate Storyline. It involved training and mentoring sessions which encompassed observation, sharing knowledge, and evaluation. These measures aimed at improving teachers’ understanding and skills in using Articulate Storyline to develop interactive instructional media for improved students' problem-solving skills. As evidenced by a 2-tailed paired sample test, the training and mentoring have been proven effective to improve teacher competence to augment students' problem-solving skills (p 0.000).